2005
DOI: 10.1002/sia.2060
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of O2, CO and CO2 with Co films

Abstract: Metastable impact electron spectroscopy (MIES), ultraviolet photoelectron spectroscopy (UPS(HeI)) and x-ray photoelectron spectroscopy (XPS) were applied to study the interaction of O 2 , CO and CO 2 with Co films at room temperature. The films were produced on Si(100) surfaces under the in situ control of MIES, UPS and scanning tunnelling microscopy (STM). For O 2 , dissociative adsorption takes place initially and then incorporation of oxygen starts at exposures of ∼5 L. Comparison of the MIES and UPS spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The complex adsorption kinetics should contain the possibility to incorporate oxygen into the film. The incorporation of oxygen in Co has been reported recently for oxygen exposure on Co/Si(1 0 0) films [15]. Moreover, the formation of different oxidation states at various substrate temperatures was revealed for oxygen on Co/W(1 1 0) films [16].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The complex adsorption kinetics should contain the possibility to incorporate oxygen into the film. The incorporation of oxygen in Co has been reported recently for oxygen exposure on Co/Si(1 0 0) films [15]. Moreover, the formation of different oxidation states at various substrate temperatures was revealed for oxygen on Co/W(1 1 0) films [16].…”
Section: Resultsmentioning
confidence: 96%
“…Iridium is therefore an excellent substrate giving the possibility for manipulating the oxidation process of clusters and films on it. By increasing the oxygen exposure of Co films supported on a Si(1 0 0) surface, the dissociative adsorption followed by incorporation of oxygen has been recently reported [15]. Moreover, modifications of surface magnetism, depending on the chemical state of oxygen, have been reported for oxygen exposed Co/W(1 1 0) films [16].…”
Section: Introductionmentioning
confidence: 97%
“…These films were then exposed to O 2 , CO, and CO 2 , again under in situ control of MIES/UPS. A detailed presentation of the results will be the subject of a future publication; 19 only a short summary will be presented here. Briefly, formation of Co-O bonds during the film oxidation produces MIES/UPS spectra that are very similar to those for the corresponding O-Ni system.…”
Section: Investigation Of the Particle Shell Studies On Bare And Gas-mentioning
confidence: 97%
“…3. The identification of the emission seen between 0 and 5 eV as due to ionization of 3d Co 2+ states 19 is of particular importance for the interpretation of the spectra from the pre-stabilized and the peptized cobalt particles. CO adsorbs molecularly, manifesting itself in two peaks 5σ ; 1π (7.5 eV) and 4σ (10.7 eV) (Fig.…”
Section: Investigation Of the Particle Shell Studies On Bare And Gas-mentioning
confidence: 99%
“…A detailed presentation of the results and their interpretation can be found elsewhere. [34] Secondly, pre-stabilized Co nanoparticles were deposited on SiO x substrates from suspensions in toluene. [35] STM indicated that a closed layer of the particles was obtained.…”
Section: Mies and Upsmentioning
confidence: 99%